Zombie in love - DiPucchio, Kelly S.; Campbell, Scott, 1973- (New York : Atheneum Books for Young Readers, 2011)
When all his efforts to find a sweetheart fail, Mortimer the zombie decides to place an ad in the newspaper.
Keywords: Zombies -- Fiction; Zombies -- Fiction; Humorous fiction; Humorous fiction